Comperation of Repelent Power of Orange Leaf Extract (Citrus Aurantifolia) and Nilam Leaf Extract (Pogostemon Cablin Benth) Toward Aedes Aegypti Mosquito - Ni Luh Ayu Meryanti; Nur Rismawati (Journal of Public Health and Pharmacy)
In this study, the research problems (1) How is the repulsion power of lime leaf extract (Citrus aurantifolia) and patchouli leaf (Pogostemon cablin benth) compared to Aedes aegypti mosquito?The objetives to be achieved ere (1) To find   out the comparison of the repulsion power of lime leaf extract (Citrus aurantifolia) with patchouli leaf (Pogostemon cablin benth) against Aedes aegypti mosquitoes (2) To determine the repulsion power of lime leaf extract (Citrus aurantifolia) against Aedes aegypti  mosquitoes  (3)  Knowing the effectiveness  of patchouli leaf extract (Pogostemon cablin benth) toward Aedes aegypti Mosquito.